PREDIKSI FINANCIAL DISTRESS PADA PT. BANK RAKYAT INDONESIA (Persero) TBK. SEBELUM DAN SEMASA PANDEMI COVID-19 - Didi Rahmat (Jurnal Ekonomi STIEP, 2021)
This study aims to see how the financial performance of PT. Bank Rakyat Indonesia (Persero) Tbk. studied from the Financial Distress approach. The data taken is from the period 2017 to 2019 (normal period) and 2020 (the period of the Covid-19 pandemic in Indonesia). Altman Z Score is used as an approach in data analysis by using five indicators, Working capital to total assets (WCTA), Retained earnings to total assets (RETA), Earnings before interest and taxes to total assets (EBITTA), Market Value of equity / Book value of debt (MVEBVD) and Sales / total assets (SATA). From the results of data analysis, it was found that before the Covid-19 pandemic the company was classified as healthy. Changes occurred during the Pandemic the company was in the Gray Area which meant there were financial problems.